O livro como objeto artístico : perspectivas do livro-poema de Wlademir Dias-Pino na arte contemporânea - Martins, Priscilla Guimarães (2016)
This work presents a study on the concept of book-poem, coined by the poet and artist Wlademir Dias-Pino in the context of the concrete poetry movement that occurred in the 1950s and 1960s in Brazil. From this, it elaborates a reflection on the developmen